P174 Effects of transcranial direct current stimulation (tDCS) intensity on vigilance performance. Issue 3 (March 2017) - McKinley, R.; McIntire, L.; Tabares, B.; Nelson, J.; Greier, B.; Harshman, S.; Goodyear, C.
Abstract : Introduction: Previously, evidence suggests that transcranial direct current stimulation (tDCS) can preserve vigilance performance for up to 6 h. However, the stimulation paradigm utilized in these studies may not be optimal. For example, Cuypers et al. (2013) found there may be more pronounced performance effects at lower tDCS intensities. The goal was to elucidate these effects and attempt to uncover biomarkers that correlate with performance. Objectives: The purpose of this effort was to (1) quantify the effects of transcranial direct current stimulation (tDCS) intensity on vigilance performance, (2) measure the duration of tDCS after effects on vigilance, and (3) survey changes in biomarkers found in breath and establish correlations between biomarkers and tDCS intensity and vigilance performance. Patients & methods: A within subjects experimental design was utilized with factor "stimulation intensity level" tested at 6 levels. The levels included tDCS at: (1) 0.5 mA, (2) 1 mA, 3) 1.5 mA, (4) 2 mA, (5) Sham, and (6) no electrodes/stimulation applied for 30 min. Participants performed a vigilance test during each visit. On each visit, they arrived at 0800 and performed the vigilance task while receiving one of the 6 randomized tDCS treatments. They provided breath samples before and after the test. Participants returned at 1600 for follow-up testing (no tDCS) and provided another breath sample. Results: A one-way ANOVA revealed there was a significant effect of tDCS intensity on vigilance target detection accuracy ( p < 0.05). Post-hoc t-tests showed that accuracy was greater at 2 mA when compared to the other intensity levels. There were no significant differences in accuracy between tDCS intensity levels during the follow-up test. Concentrations of a substance in breath known as 1-proponol was found to be significantly lower at 2 mA when compared to sham tDCS. Conclusions: The evidence suggests tDCS applied at 2 mA significantly improves vigilance performance. However, this effect is completely gone 8 h later. This supports previous evidence suggesting the effect of tDCS on vigilance is approximately 6 h. Additionally, a protein in breath was discovered whose concentrations correlate with performance and tDCS intensity. Hence, this could be a biomarker capable of monitoring operator vigilance state.